Electron paramagnetic resonance dosimeter material properties of potassium hydrogen tartrate and potassium tartrate hemihydrate - Wong, Jia Ding (2021)
The electron paramagnetic resonance (EPR) of potassium hydrogen tartrate (PB) and potassium tartrate hemihydrate (PT) as a EPR radiation sensitive material was investigated. The aim of this study is to find a new bone-equivalent dosimeter material in clinical use. PB and PT irradiated with X-ray were studied. The energy dependence, dose-response, and radical stability of PB were studied. The simulation data was verified with the experimental data in order to study the capability of the spectra generated by the EasySpin. Both samples were exposed to X-ray in the range of absorbed dose, 1 - 9 Gy. The data measurement for EPR spectra was conducted 24 hours after the irradiation process. The energy dependence of PB sample is equivalent to the energy dependence of bone from 1 keV to 2 keV and above 100 keV to 1 MeV while the energy dependence of PT is bone-equivalent from 1 keV to 2 MeV and from 5 keV to 1 MeV. The features of the spectrum for PT sample that irradiated with X-ray is the same as that irradiated with gamma ray in the previous study. For PT samples, 3 peaks were observed and second peak was used throughout the study. The g-factor of PT samples was 2.00316 ± 0.00024. There were 2 peaks obtained from the spectrum of PB sample. First peak was used throughout the study. The g-factor obtained in this study for PB sample was 2.00942 ± 0.00130. The effect of the modulation amplitude and microwave power was studied within the range of 0.2 - 2 mT and 0.1 - 5 mW, respectively. In order to obtain the optimum EPR spectra, the selected modulation amplitude and microwave power were 0.7 mT and 0.6 mW, respectively. Linear dose-response was yielded for PT sample irradiated with X-ray between the dose range of 1 - 9 Gy while linear dose-response is obtained between the dose range of 2 - 9 Gy for X-ray irradiated PB sample. The normalised signal intensity of PT sample that irradiated with X-ray was higher than that irradiated with gamma ray. The signal of PB sample increased in the first 10 days after irradiation and maintained at a stable value for at least 50 days after irradiation. The EPR spectra generated by the simulation is the same as the experimental result. Nevertheless, the simulation had showed that 0.8 mT is the optimum modulation amplitude. This value is different with the value of experimental optimum modulation amplitude because the factor of signal-to-noise ratio and the simulation does not include the parameter of microwave power, as mentioned in previous study. In conclusion, PB sample is not that suitable for medical usage for low dose measurement that lower than 1 Gy. The higher absorbed dose range and potential voltage, or changing the radiation source to gamma rays, and the effect of temperature with relative humidity during the irradiation process is worth to be studied in the future.